ANALISIS PENGAMANAN BARANG MILIK DAERAH ASET TETAP TANAH DALAM MENINGKATKAN TERTIB ADMINISTRASI PADA DINAS PEKERJAAN UMUM DAN PENATAAN RUANG KABUPATEN ENDE - Lalo, Serliana Doy Bay; Djou, Laurentius D. Gadi; Soleiman, Iriany Dewi (Program Studi Akuntansi Universitas Flores, 2024)
The problem formulated in this study is that the Public Works and Spatial Planning (PUPR) office of Ende Regency has not fully secured the property of the area of land fixed assets where there is still land that has not been made a certificate and land that has noot been made a boundary fence and has not taken care of land assets. This study aims to identify and describe the security of fixed assets in the form of land in improving administrative order at the Public Works and Public Housing Agency, Ende Regency. The method used is descriptive qualitative method with an inductive approach to describe the research object based on facts in the field. Bades on the results of the research conducted, the security of fixed assetd in the form of legal security and administrative security. The suggestion given by the researcher is to make a temporary certificate as a reserve for administrative purposes.